GLOBAL BIOPROGRESSIVE REHABILITATION PROGRAM AND POSTURAL INSTABILITY IN PARKINSON’S DISEASE - Bellomo RG; Di Pancrazio L; Khodor H; Saggini R; Barassi G; Carmignano SM; Di Stefano A (European Scientific Journal, ESJ, 2014)
Postural instability increases the risk of falling. Falls are common events in Parkinson disease (PD) but only a few prospective studies have focused on causes and consequences of falls. Frequent falls represent a major problem for PD patients, causing head traumas and bone fractures. Different rehabilitative strategies have been tentatively applied, especially on visual disturbances, but more structured studies are needed to quantify the efficacy of specific physical treatments. Objective: To create a bioprogressive rehabilitation program effective to influence in a positive way the quality of life through the recovery of postural control, the use by the patient of a more stable scheme of walking and less demanding from the point of view of the energy necessary, a raise of the muscular strength and resistance and a raise of the mobility. Ultimately the goal is to reduce the risk of falling and the spiral of events linked to the hypokinetic syndrome that can follow the event fall. Methods: 12 PD patients were randomly selected. The patients underwent dynamic antigravity postural system (SPAD) associated with an auditory cue system (a metronome) and the highintensity focused vibratory system (VISS) and VRRS (Virtual Reality Rehabilitation System, active stretching treatments for 4 months. Results: The bioprogressive rehabilitation program has determined an improvement of balance of the patients while walking so a reduction of fall and an improvement in quality of life.